PENGARUH ORGANIZATIONAL SUPPORT TERHADAP WORK ENGAGEMENT DI LAPAS KELAS IIA BOJONEGORO - Kurnianto, Ivan Julian; Kusmiyanti, Kusmiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
In managing an organization, human resources are a very important part of building an organization, and human resources are a very important factor in building a public or private organization. It can be described as employees who contribute to the functioning of the organization and work within it. Organizational Support felt by employees can influence their work engagement. The purpose of this research is to determine the influence of Organizational Support on Work Engagement. The Bojonegoro Class IIA Prison was chosen to be the locus of the research. The method used in this research is quantitative through distributing questionnaires to respondents. The sample used in this research was 61 respondents. There are 2 variables examined in this research, namely Organizational Support (X) and Work Engagement (Y). From the results of the data processing carried out, it is known Organizational Support affects Work Engagement in Class IIA Bojonegoro Prison, with an influence level (R-Square) of 27.2%. Keywords: Organizational Support; Work Engagement; Prison